Summary: EFTA-TIC Conference - Grajina Budinaite; Anna Varga; Elena Chebotareva (Психология и Психотерапия Семьи)
On October 19-20, 2024, the meeting of the Training Committee of the European Association of Family Psychotherapists EFTA-TIC was held in Lisbon, Portugal. These meetings are held regularly, this was the 14th. OSKiP is an associate member of EFTA-TIC. At the conference, OSKiP was represented by Grajina Budinaite (OSKiP board member), academic director of the Master's program in Systemic Family Psychotherapy at the HSE, Elena Chebotareva (OSKiP member), and Anna Varga (OSKiP board member). All of them are teachers of the Master's program "Systemic Family Psychotherapy" at the National Research University Higher School of Economics.